Exploring the impact of comorbidities and drug resistance on mortality in ICU-acquired bloodstream infections - Sharifzadeh Kermani, Mahdieh; Pouradeli, Shiva; Sadeghian, Reihaneh; Momen Abadi, Zahra (AMB Express, 2025)
Hospital-acquired bloodstream infections (BSIs) seriously challenge critically ill patients. These infections in the ICU lead to significant morbidity, mortality, increased costs, and prolonged hospital stays. Therefore, the present study investigated this condition's prevalence and risk factors. This cross-sectional study was conducted on patients with neurological and nephrological issues admitted to general ICUs and trauma patients in two large hospitals in southeastern Iran. Bacteremia prevalence and mortality effects in ICU patients were analyzed from March 2020 to September 2022 during the COVID period. The results identified 127 patients with positive blood cultures, including 59 from the general ICU and 68 from the trauma ICU, yielding prevalences of 3.02% and 1.93%, respectively. The most common comorbidities included drug addiction (36.2%), chronic hypertension (35.4%), and type 2 diabetes (25.2%). Klebsiella pneumoniae was the most frequently isolated organism, followed by Staphylococcus epidermidis, Staphylococcus aureus , and Acinetobacter . The mortality rate was 93.2% in the general ICU and 60.3% in the trauma ICU. Risk factors associated with mortality included diabetes, hypertension, renal failure, drug addiction, a history of surgery in the last 30 days, ineffective experimental antibiotic treatment, and the administration of vasopressors. The prevalence of multiple drug resistance (MDR) was 33%, while Vancomycin-Resistant Enterococcus (VRE) was found in 9.4% of cases. These findings suggest that identifying and controlling risk factors associated with bacteremia in ICU patients is essential for reducing mortality.